2014
DOI: 10.1016/j.neuroimage.2013.09.024
|View full text |Cite
|
Sign up to set email alerts
|

A key region in the human parietal cortex for processing proprioceptive hand feedback during reaching movements

Abstract: Seemingly effortless, we adjust our movements to continuously changing environments. After initiation of a goal-directed movement, the motor command is under constant control of sensory feedback loops. The main sensory signals contributing to movement control are vision and proprioception. Recent neuroimaging studies have focused mainly on identifying the parts of the posterior parietal cortex (PPC) that contribute to visually guided movements. We used event-related TMS and force perturbations of the reaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 62 publications
(115 reference statements)
3
27
0
Order By: Relevance
“…Therefore, it seems that this activation might indicate a neural substrate of the encoding of the kinematics of movements. Such activity is in agreement with previous studies that reported increments of activity over the posterior parietal cortex (PPC) in sensorimotor processes during visuomotor reaching movements (Reichenbach et al, 2014). However, to our knowledge, we report by first time a clear relationship between this neural activity and the kinematics of the movement, concretely the achievement of the peak velocity.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it seems that this activation might indicate a neural substrate of the encoding of the kinematics of movements. Such activity is in agreement with previous studies that reported increments of activity over the posterior parietal cortex (PPC) in sensorimotor processes during visuomotor reaching movements (Reichenbach et al, 2014). However, to our knowledge, we report by first time a clear relationship between this neural activity and the kinematics of the movement, concretely the achievement of the peak velocity.…”
Section: Discussionsupporting
confidence: 93%
“…From a Bayesian perspective, it can be argued that it is advantageous to maintain multiple representations of movement parameters, expressed in diverse reference frames, in order to optimize motor performance. Electrophysiological evidence also supports the notion that motor planning and execution is carried out in multiple reference frames in parallel, both across different regions of the brain and within a single cortical area (Buneo et al, 2002; Beurze et al, 2010; Buchholz et al, 2013; Maule et al, 2013; Reichenbach et al, 2014). At the behavioral level, the fully convergent model depicted in Figure 6A cannot predict certain experimentally observed characteristics of movement planning and execution.…”
Section: Discussionmentioning
confidence: 58%
“…In the current study, better deviation detection sensitivity (as quantified by the d 0 measure) correlated positively with gray matter volume of both occipital and parietal areas. These regions are likely to play an important role in the integration of visual and somatosensory information during visuomotor performance, and overlap with those activated by reaching to a visual target in tasks similar to ours (Reichenbach, Thielscher, Peer, Bulthoff, & Bresciani, 2014). For instance, Lacquaniti et al (1997) performed a PET study where participants had to either visually detect or manually point to a target in a sequence.…”
Section: Discussionmentioning
confidence: 95%